DNA-catalysed alternative RNA splicing. Issue 55 (21st June 2022) - Wei, Dongying; Gao, Mingmei; Guo, Jiajie; Wang, Yueyao; Li, Xintong; Li, Zhe; Yu, Hanyang
Abstract : DNA can catalyse alternative RNA splicing reactions in vitro, and modulate RNA structure and function. Abstract : We report DNA-catalysed alternative RNA splicing in vitro . Using modular DNA catalysts with RNA endonuclease and RNA ligase activities, we show that DNA can modulate RNA structure and activity. Furthermore, we illustrate that such DNA-catalysed reactions can yield, from a common precursor, different splicing isoforms with distinct functions.